ASSESSING THE IMPACT OF VIRTUAL PLATFORMS ON DIGITAL LEXICAL DEVELOPMENT: A CRITICAL ACADEMIC REVIEW - BERDIKULOVA MUNIRA AZIZOVNA (TADQIQOTLAR, 2026)
ABSTRACT: This paper evaluates how web-based digital environments influence vocabulary mastery and long-term memory encoding among non-native language learners (EFL/ESL). By analyzing current trends in computer-assisted pedagogy, the study examines the real-world utility of gamified software, algorithmic spaced-repetition cards, and immersive web portals. The analysis indicates that multi- sensory online tasks significantly improve semantic mapping and lower communicative anxiety compared to traditional textbook drills. However, the study also highlights important pedagogical concerns, such as student cognitive fatigue, the brief lifespan of tech-driven motivation, and the persistent gap between word recognition and active conversational use. Finally, the author offers practical frameworks for combining online learning with active classroom communication.